Análise dos aplicativos Uber e 99pop em relação aos usuários do transporte público de Uberlândia (MG) - Mascarenhas, Rafhael Ribeiro (2023)
The present study evidences the result of transformations engendered in urban space by ICTs - Information and Communication Technologies, which englobes mediating technologies in communication processes enhanced by internet and smartphone use in last two decades. It aims to analyze the technology companies – startups Uber and 99Pop regarding the public transport in Uberlandia-MG, projecting a social and economic overview of users reprodution about this recent modal, seeking to understand how intra-urban demands have given new meaning in the municipality. Firstly, we proposed a discussion about the spread of ICTs and setting of cyberspace, such as internet use by smartphones, leding the use of these recent services in the cities. Afterwards, we reinforced the relevance of mobility beyond brazilian metropolitan regions, highlighting Uberlandia as a relevant space in transition from medium to large, symbolized by a robust logistical junction in the center of Brazil, allied by its horizontal growth fueled by interests of local elites. For this study, we highlight the increase of motorized fleet and the use of ride-sharing application platforms as the main factors, which set a new meaning to the permanent demands and flows of traditional mobility, simbolized by public transport. Based on methodologies that supported criteria for the collection and classification of sample data per interview, we present in a stratified manner the income profile of users of Uber and 99Pop apps by sectors and salary ranges. That way, given the adversities foreseen in a geographical survey that focuses on urban mobility, the social and economic aspect based on the average income of users was the central criterion adopted to analyze the use of these apps in order to public transport. Based on the profiles outlined, we evidenced the microdynamics on intra-urban scale, whose hypothesis points out that the services provided that the Technologies Companies are mostly complementary to public transport in all sectors of the city, even recording cases of disruption and discrepant data for a given range of income. We also highlight that the quality of urban public transport in Uberlandia reflects policies that encouraging individual motorized vehicles, such as public authorities and concession companies negligence, eliminating users who have not other modal option for longer urban trips, and those who use paid ride-hailing apps as a modal migration.